The Role of the Maluku Province Education Office in Meeting the Needs of Civics Subject Teachers - Tuna, Rahma; Soumokil, A; Tuharea, Jumiati (Jurnal Pendidikan Amartha, 2023)
Civics subjects are also one of the important subjects that must be taught by teachers who have a Civic Education background, this is important because currently the younger generation has lost their sense of nationalism, in the midst of modernization and globalization of the times. Therefore, the role of not only the Principal is needed but the role of the region, one of which is regulated and managed by the region is the field of education, as in Law number 32 of 2004 concerning regional government article 14 paragraph 1 it is stated that the Implementation of Education is one of the mandatory affairs that is the authority of the Provincial Government and Regency / City government. And regulated in law number 14 of 2005 concerning Teachers and Lecturers, in article 24 paragraph 2 it is stated that the provincial government is obliged to meet the needs of teachers, both in number, academic qualifications, as well as in competence equally to ensure the continuity of secondary education and special education in accordance with their authority. The problem in this study is how the role of the Maluku provincial education office in meeting the needs of Civics subject teachers at SMA Negeri 16 Seram Barat, Manipa Islands District, West Seram Regency. The method used in this study is qualitative research method. The data collection technique that the author did consisted of two ways, namely observation and interview. The data analysis technique that the author used in this study is interactive data analysis. The results of the research obtained by the author are: The role of the education office in meeting teacher needs is by conducting recruitment of honor personnel or contract teachers and recruitment of CPNS and PPPK in accordance with the provisions of the Law.